2008
DOI: 10.1007/s11515-008-0044-8
|View full text |Cite
|
Sign up to set email alerts
|

Microbial diversity in lake sediments detected by PCR-DGGE

Abstract: In this study, PCR-denaturing gradient gel electrophoresis (DGGE) was applied to analyze the microbial communities in lake sediments from Lake Xuanwu, Lake Mochou in Nanjing and Lake Taihu in Wuxi. Sediment samples from seven locations in three lakes were collected and their genomic DNAs were extracted. The DNA yields of the sediments of Lake Xuanwu and Lake Mochou were high (10 mg/g), while that of sediments in Lake Taihu was relatively low. After DNA purification, the 16S rDNA genes (V3 to V5 region) were am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
(3 reference statements)
1
6
0
Order By: Relevance
“…Moreover, being pathogenic members of the coliform bacteria, they pose a real public health risk through direct contact with this soil or the crops produced from it. These results are consistent with those of Joynt et al (2006), Zhao et al (2006) and Mocali et al (2008) where pollution shifted the indigenous population to more resistant Gram-positive species mainly Bacillus and Brevibacillus ([83%) as well as Acinetobacter. In contrast to Mocali et al (2008), in the present study the dominant identified species were Gram-negative, non-spore-forming bacteria which confirmed that their dominance and resistance resulted from selective pressure of microbial species with a set of genes involved in biodegradation of such contaminants and their ability to use them as energy sources.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Moreover, being pathogenic members of the coliform bacteria, they pose a real public health risk through direct contact with this soil or the crops produced from it. These results are consistent with those of Joynt et al (2006), Zhao et al (2006) and Mocali et al (2008) where pollution shifted the indigenous population to more resistant Gram-positive species mainly Bacillus and Brevibacillus ([83%) as well as Acinetobacter. In contrast to Mocali et al (2008), in the present study the dominant identified species were Gram-negative, non-spore-forming bacteria which confirmed that their dominance and resistance resulted from selective pressure of microbial species with a set of genes involved in biodegradation of such contaminants and their ability to use them as energy sources.…”
Section: Discussionsupporting
confidence: 89%
“…The PCR-DGGE or PCR-DHPLC (as in the present study) techniques combined with sequence analysis are a feasible and efficient method for the determination of microbial communities in environmental samples and differentiation of the very closely related species (Zhao et al 2006;Mocali et al 2008;Wang et al 2008;Yin et al 2008;Zhang et al 2008). However, it is obvious that due to the hazardous effect of pollution, only a low percentage of the microbial population is cultivable.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…For the assessment of sediment environmental stress, bacterial community may be function as indicator organisms because sediment provides substrate for bacterial colonization and nutrients for bacterial growth (Atlas 1984;Kassen and Rainey 2000;Kemp and Aller 2004;Kostanjšek et al 2005). In the recent years, molecular biological tools like denaturing gradient gel electrophoresis (DGGE) and temporal temperature gradient electrophoresis (TTGE) have become popular for bacterial community analysis in sediments due to their effectivity to monitor bacterial structure changes (Torsvik et al 2002;Freitag and Prosser 2003;Kostanjšek et al 2005;Zhao et al 2008;Ikenaga et al 2009). The methodological protocols are mainly based on sequencing analyses of 16S ribosomal DNA (rDNA) fragments from dominant electrophoresed bands on a gel.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a brighter band signal suggested a higher richness of the species. Therefore, we could obtain information about the number of dominant species and quantity of microbes in the samples (Zhao et al, 2008). The DGGE patterns were showed in Fig.…”
Section: Amplification Of Endophytic Bacterial 16s Rdnamentioning
confidence: 99%